Conceptual structural design bridging the gap between architects and engineers - Larsen, Olga Popovic (Thomas Telford, 2003)
This volume bridges the gap between engineers' and architects' understanding of structural form. It aims to inspire designers to develop innovative and viable structural forms. It presents the common issues and problems faced and demonstrates how to overcome them by using high profile case studies.